IEEE Local Computer Network Conference 2010
DOI: 10.1109/lcn.2010.5735838
|View full text |Cite
|
Sign up to set email alerts
|

Experiments with wireless sensor networks for real-time athlete monitoring

Abstract: Abstract-Real-time physiological monitoring of athletes during sporting events has tremendous potential for maximizing player performance while preventing burn-out and injury, and also enabling exciting new applications such as referee-assist services and enhanced television broadcast. Emerging advanced monitoring devices have the right combination of light weight and unobtrusive size to allow truly non-intrusive monitoring during competition. However their small battery capacities, limited wireless ranges and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
4
3
2

Relationship

2
7

Authors

Journals

citations
Cited by 26 publications
(15 citation statements)
references
References 16 publications
(15 reference statements)
0
15
0
Order By: Relevance
“…Apart from medical applications, real-time healthcare monitoring is in high demand for sport where a personalized training plan for each athlete should be developed by coaches to improve the performance of their team, especially at an elite level. To this end, the physiological capabilities, physical activities, and vital signs of athletes need to be closely monitored and recorded by the coaches through long-term monitoring [5]. According to a report by ABI Research, the market for sports and fitness-related monitoring devices is projected to reach 80 Currently, multiple sensors attached to different body locations for monitoring patients' vital signs are widely used in health care monitoring due to their high recognition accuracy and low computational load [7].…”
Section: Introductionmentioning
confidence: 99%
“…Apart from medical applications, real-time healthcare monitoring is in high demand for sport where a personalized training plan for each athlete should be developed by coaches to improve the performance of their team, especially at an elite level. To this end, the physiological capabilities, physical activities, and vital signs of athletes need to be closely monitored and recorded by the coaches through long-term monitoring [5]. According to a report by ABI Research, the market for sports and fitness-related monitoring devices is projected to reach 80 Currently, multiple sensors attached to different body locations for monitoring patients' vital signs are widely used in health care monitoring due to their high recognition accuracy and low computational load [7].…”
Section: Introductionmentioning
confidence: 99%
“…In [26] WSN has been used to monitor the performance of rowers on boats and compare performances amongst team members. Dhamdhere et al [27] have also implemented WSN to monitor football players and transmit real-time information to the sideline. However the emphasis was on routing and their results showed that the time delay to deliver information from players to the sideline was unacceptably long due to the multi-hop routing technique used.…”
Section: Introductionmentioning
confidence: 99%
“…Our current work in [27] develops multi-hop routing schemes appropriate for soccer player monitoring. We will also undertake further experimental work replacing the Crossbow motes with wearable body-area networking devices as they become available.…”
Section: Discussionmentioning
confidence: 99%